#CybillToo?: how a feminist sitcom (almost) exposed Hollywood's dark secrets. Issue 2 (3rd July 2021) - Kypker, Nicole S.
Abstract: The sitcom Cybill (CBS 1995–1998) is loosely based on the real-life experiences of its feminist star and executive producer, Cybill Shepherd. The show thus has the extraordinary potential to relate the experiences of a Hollywood actress, operating within a singularly influential apparatus in the creation of dominant ideologies, including representations of women. This 'belly of the beast' set-up suggests an abundance of possibilities for the woman buffoon, trickster or thief of language to tell her thus-far censored, inside story, but within a medium and textual format that are themselves significantly controlled by, and instrumental in perpetuating, that very same machinery. Yet this sitcom was produced in the nineteen-nineties, a decade characterised by apolitical, postmodern irreverence. This article will assess the sitcom's integration of postmodern, conservative and feminist discourses by conducting a critical discourse analysis, as formulated by Norman Fairclough, of one episode. The episode is one of two in which the show depicts Hollywood producers requesting sexual favours in return for employment opportunities, two decades before the practice provoked international outrage and brought about the formation of the #MeToo movement. The episode overall adopts a morally dubious positioning in its portrayal of Hollywood realities. However, as will be argued, this very postmodern ambiguity enabled the sitcom to represent and denounce long-established 'casting couch' practices, if in a cursory and trivialising manner.